From Southern Bluefin Tuna Case to Biodiversity Beyond National Jurisdiction (BBNJ) - Dowsuwan, Sumullika; Sukhum, Juntratip (University Of Bengkulu Law Journal, 2023)
This paper aims to study the prescription of provisional measure of International Tribunal for the Law of the Sea (hereinafter ITLOS) on Southern Bluefin Tuna case between New Zealand and Japan; Australia and Japan. Moreover, this case concerns the Southern Bluefin Tuna (hereinafter Bluefin Tuna) fishing, Japan’s experimental fishing program exceed the set level by parties and the approach of ITLOS can clarify the example of the circumstance in order to take a provisional measure to prevent serious harm to the marine environment. The results show that this case can illustrate the approach of ITLOS to take a provisional measure as follow: tribunal shall take into account the circumstances to lead a serious harm to the marine environment. Additionally, this dispute, the circumstance of Japan exceeded Bluefin Tuna fishing, it brings about to be the serious harm to the marine environment. Thus, ITLOS notes that Japan, New Zealand and Australia should take the effective conservation measure in order to prevent serious harm to the stock of Bluefin Tuna because the conservation of the Bluefin Tuna is an element of protection and preservation of the marine environment. Nowadays, Biodiversity Beyond National Jurisdiction (hereinafter BBNJ) helps to preserve and protect the Bluefin Tuna as marine environment for the next generation also.